Modeling of Tool Wear when Turning of TI-6AL-4V Titanium Alloy - Al Hassani, Azza Rashed (2013)
A Master of Science thesis in Mechatronics Engineering by Azza Rashed Al Hassani entitled, "Modeling of Tool Wear when Turning of TI-6AL-4V Titanium Alloy," submitted in February 2013. Thesis advisor is Dr. Ibrahim M. Deiab and thesis co-advisor is Dr Khaled Assaleh. Available are both soft and hard copies of the thesis.